POTENSI SAYUR ORGANIK LOKAL DAERAH RAWA DI KALIMANTAN TENGAH: “MANFAAT DAN TINGKAT KESUKAAN” - Yanetri Asi Nion; Renhart Jemi; Yusurum Jagau; Trisna Anggreini; Ria Anjalani; Zafrullah Damanik; Inga Torang; Yuprin Yuprin (Universitas Lambung Mangkurat, 2018)
Dayak tribe in Central Kalimantan Province has long time ago applied the local wisdom of healthy life and environmental friendly by consuming more local vegetables that grow wild. The research was conducted from July to September 2018, by conducting survey observations and interviewing respondents in Kapuas district, Pulang Pisau district, Katingan district, Gunung Mas district, and Palangka Raya city. There are a total of 14 species found from swamp areas, namely Singkah enyuh (Cocos nucifera), Singkah undus (Elaeis guineensis), Singkah hambie (Metroxylon sagu), singkah uwei (Calamus sp), Taya (Nauclea sp), Ujau (Bambusa sp), Bajei (Diplazium esculentum), Bakung (Crinum asiaticum), Kalakai (Stenochlaena palustris), Kujang (Colocasia esculenta), Uru mahamen (Neptunia olearecea), Pucuk teratai (Nymphae sp), Genjer (Limnocharis flava), dan Kangkung danum (Ipomoea aquatica). The benefits of local vegetables aside from being a food source that has the potential as a drug, pesticides, bioethanol and various other industrial materials. The majority of respondents aged over 40 years prefer vegetables (local) and food types were soup, while middle age (16-40 years) and young (under 16 years) can adapt to vegetables from outside and a new menu from outside Kalimantan. Factors for choosing the types of vegetables to be consumed are more influenced by taste reasons (54-86%), followed by habits (32-47%) and benefits for health (39-40%).